CTCF deletion alters the pluripotency and DNA methylation profile of human iPSCs - Puri, Deepika; Maaßen, Catharina; Varona Baranda, Monica; Zeevaert, Kira; Hahnfeld, Lena; Hauser, Annika; Fornero, Giulia; Elsafi Mabrouk, Mohamed H.; Wagner, Wolfgang (Frontiers in Cell and Developmental Biology, 2023)
Pluripotent stem cells are characterized by their differentiation potential toward endoderm, mesoderm, and ectoderm. However, it is still largely unclear how these cell-fate decisions are mediated by epigenetic mechanisms. In this study, we explored the relevance of CCCTC-binding factor (CTCF), a zinc finger-containing DNA-binding protein, which mediates long-range chromatin organization, for directed cell-fate determination. We generated human induced pluripotent stem cell (iPSC) lines with deletions in the protein-coding region in exon 3 of CTCF, resulting in shorter transcripts and overall reduced protein expression. Chromatin immunoprecipitation showed a considerable loss of CTCF binding to target sites. The CTCF deletions resulted in slower growth and modest global changes in gene expression, with down-regulation of a subset of pluripotencyassociated genes and neuroectodermal genes. CTCF deletion also evoked DNA methylation changes, which were moderately associated with differential gene expression. Notably, CTCF-deletions lead to up-regulation of endo-mesodermal associated marker genes and epigenetic signatures, whereas ectodermal differentiation was defective. These results indicate that CTCF plays an important role in the maintenance of pluripotency and differentiation, especially towards ectodermal lineages.